Development of problem based learning model integrated TPACK to improve problem solving ability - Edy Waluyo (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to develop of Problem Based Learning model integrated TPACK to improve problem solving ability. The research method used is Dick & Carey model development research including needs analysis, product design, product development, product implementation and evaluation. The subjects of this study were grade VIII students of SMPN 2 Selong which numbered 30 students. Instruments used to collect data include product validation guidelines, product practicality questionnaires and problem-solving ability tests on geometry materials. The data collected in this study were analyzed using descriptive analysis. Based on the data analysis carried out, the product developed is classified as valid as indicated by the average product validation score by 3 experts, namely 79.4; 79,9; and 80.8. Product trials were carried out 4 times and showed that the products developed were relatively practical. The product is also classified as effective with an effectiveness percentage of 86.67%. The developed product has a potential effect in improving mathematical problem solving ability with N-Gain of 0.81 with a high category.